THE SUPREME AUDIT INSTITUTION - Diana Elena BRINZA; Mihaela Iuliana DUMITRU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The work aims to present the internal audit activity at the level of public institutions, its scope and main objectives. On the other hand, it highlights the general methodology applicable to any internal audit mission. The pages of this Article show special features of the Supreme Audit Institution, the Court of Auditors, in the case of four EU Member States: France, Germany, Italy and Romania. For each individual State we have given information on the audited entities, the governing body, the organizational structure, the reports issued and the statement on the mission of the Court of Auditors.